Currículo integrado do curso de agroecologia no IF - Baiano Campus Valença- BA: entre o oficial e a prática cotidiana - Almeida, Leonizia de Jesus Sena de (2018)
This study investigates the construction, execution and implementation of the Integrated Curriculum of the Technical Course in Agroecology at Baiano Federal Institute of Education, Science and Technology (IF Baiano) - Campus Valença. For this investigation it was used the research of descriptive character and as method, we chose qualitative research because it implies in a means of collecting and analyzing data through various sources.The purpose of these statements is to analyze the Integrated Curriculum from official documents and practices of teachers, and to reach them, it is relevant to deepen the theoretical debate around the School Curriculum and Integrated Curriculum; to identify the knowledge addressed in the pedagogical proposal of the course as well as the menus and plans of teaching for understanding the necessity of this look, and finally, to investigate the teaching practice in the applicability of the prescribed curriculum. The locus of the research was the Agroecology Course at IF Baiano, Campus-Valença. As methodological procedures to obtain the data, a bibliographic review and analysis of IF Baiano official documents was carried out. In addition, it was used some procedures in this study: application of semi-structured questionnaire and semi-structured interviews with teachers, Course Coordinator, Teaching Coordinator and Technical-Pedagogical team. The empirical analysis of the Integrated Curriculum developed in that previously mentioned course, showed from the research findings, which it was and it continues to be a challenging practice, although some initiatives point to practices closer to the knowledge integration. In these findings, some problems of physical and pedagogical nature were mentioned that bring difficulties in the applicability of the Integrated curriculum in the Agroecology Course, such as: the lack of physical structure in the development of practical classes; the lack of a proposal for continuing training for teacher qualification; the difficulty of finding a trained professional in the specific area in order to develop the work; the organization of a coherent curricular matrix to meet the needs of the Technician in Agroecology; the time of course formation, which needs to be revised to allow more coherent pedagogical proposals, among others. It is believed that this study can contribute with reflections about possibilities for the effective construction of a Curriculum that meets the specificities of Integrated Technical Education to High School, so that it can approach coherent pedagogical practices that aim at the integration of the necessary knowledge for the student education.